Practitioner research. (c2019) - Arayssi, Sabine Imad (2019)
Teachers as practitioner researchers are marginalized in educational institutions since teachers are being subjugated by overwhelming obligations and standards which hinders their autonomy and transparency in voicing out their concerns and enhancing their practices. This study examined language teachers’ perception of practitioner research in order to establish an understanding whether research comprises a fundamental component in their career. A qualitative study was conducted with language teachers and coordinators from various schools in Lebanon. Questionnaires were distributed to 50 language teachers, followed by semi-structured interviews conducted with language coordinators, and in-depth interviews with language teachers who are practitioner researchers. Results indicate that research is a minority activity for language teachers due to the common issues which are lack of time, overwhelming working conditions, and lack of flexibility in the workplace. Limitations and recommendations for promoting practitioner research among language teachers are further discussed at the end of the study.